To find the solution of the system of equations given the two equations represented by the y-values, we will look for a common (x, y) pair in the two sets of y-values.
From the table:
-
For \(y = 2x - 5\):
- When \(x = 0\), \(y = -5\)
- When \(x = 1\), \(y = -3\)
- When \(x = 2\), \(y = -1\)
- When \(x = 3\), \(y = 1\)
-
For \(y = x - 3\):
- When \(x = 0\), \(y = -3\)
- When \(x = 1\), \(y = -2\)
- When \(x = 2\), \(y = -1\)
- When \(x = 3\), \(y = 0\)
Now, let's compare the y-values from both equations for each x-value:
- At \(x = 0\): \(y = -5\) (from \(y = 2x - 5\)) and \(y = -3\) (from \(y = x - 3\)) — not a solution.
- At \(x = 1\): \(y = -3\) and \(y = -2\) — not a solution.
- At \(x = 2\): \(y = -1\) and \(y = -1\) — this is a solution! \((2, -1)\)
- At \(x = 3\): \(y = 1\) and \(y = 0\) — not a solution.
The pair \((2, -1)\) is the only point where both equations meet, thus it is the solution to the system of equations.
Therefore, the answer is: \((2, -1)\)